Structural, Physicochemical, and Functional Properties of Dietary Fiber Extracts from Euryale ferox - Meng YUAN; Xiaoqian LIU; Hao ZHANG; Xinyi HE; Jiangtao LIN; Qinghua YUE (Shipin gongye ke-ji)
This study focused on the soluble and insoluble dietary fibers extracted from Euryale ferox, and compared them with wheat dietary fiber, aiming to comprehensively analyze the structure, physicochemical properties, and functional characteristics of Euryale ferox dietary fiber. The structural characteristics of the dietary fibers were analyzed by technical means such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR). Simultaneously, their antioxidant properties, glucose and cholesterol adsorption capacities, enzyme activity inhibition capabilities, and rheological properties were evaluated. The results indicated that the insoluble dietary fiber from Euryale ferox (GIDF) exhibited high crystallinity (31.86%), a compact structure, small particle size, and large surface area, demonstrating excellent water holding capacity (4.54±0.07 g/g) and oil holding capacity (3.82±0.35 g/g). In rheological analysis, both the dietary fibers from Euryale ferox and wheat exhibited shear-thinning behavior. The SDF (soluble dietary fiber) samples displayed low stiffness, high damping properties and viscoelastic behavior, and high viscosity and frequency sensitivity. Compared to wheat soluble dietary fiber (WSDF), the G' and G'' of the soluble dietary fiber from Euryale ferox (GSDF) were higher, suggesting that the molecular chains or network structures in GSDF were more compact and ordered, enabling better resistance to deformation. Furthermore, GSDF exhibited high α-amylase inhibitory activity, hypoglycemic activity in vitro, cholesterol adsorption capacity, and radical scavenging ability. In summary, compared to wheat dietary fiber, the dietary fiber from Euryale ferox demonstrated significant advantages in both structural and functional characteristics, particularly in its antioxidant capacity, hypoglycemic capacity in vitro, and inhibition of α-amylase activity. These findings provide strong support for the potential application of dietary fiber from Euryale ferox in the food industry.